Emerging Communist Ideology and Ideas in The Press and Artistic Literature in Turkestan in The 20s-30s Of The 20th Century - Temur Jamoliddinov (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article describes the events of the 20s and 30s of the 20th century in Turkestan during the Bolshevik invasion, the policy of Vladimir Lenin and Stalin. The deplorable condition of ideological, political, religious, socio-economic, educational, scientific, cultural, women's issues, and the shortcomings of the press and fiction literature are discussed as well.